KEKUATAN PEMBUKTIAN AFFIDAVIT SEBAGAI ALAT BUKTI SURAT - Endah Puspita Sari (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract The process of verification carried out against anyone who argues against a right or events and to affirm their rights or to deny the right of another person shall be proved for the right or the event. Evidence in a civil case that there are five letters or written evidence, witness evidence, conjecture, confession and oath. Fifth kinds of evidence that, in principle, judges in the trial of civil cases should give ample opportunity to the litigants is to propose a means of evidence to support their arguments and rebuttal lawsuit, therefore, the role of evidence in the trial very important role to prove a disputed event. The next steps are the judges examine, assess, consider and decide all that in its decision. Problems arise when the Affidavit in use as evidence in the trial. The problem of this research is how the strength of evidence affidavit as documentary evidence. The purpose of this research is to know, understand, and analyze the strength of evidence affidafit as documentary evidence. This research method is a normative legal research. Based on the results of the discussions conducted by the authors that the affidavit is a written statement made under oath and under the authority of the Notary public that embraces the common law system. categorized as documentary evidence or written because the physical form submitted at the hearing that the written and still as usual documentary evidence. Affidavit can not stand alone for evidence in court, therefore, should be assisted by other evidence such as witness testimony, the evidence conjecture, evidence recognition, and evidence oath. Key words: verification, evidence, and affidavit Abstrak Proses pembuktian dilakukan terhadap barang siapa mendalilkan terhadap suatu hak atau peristiwa dan untuk meneguhkan haknya atau guna membantah hak orang lain haruslah dibuktikan adanya hak atau peristiwa tersebut. Alat bukti dalam perkara perdata ada lima yaitu alat bukti surat atau tulisan, alat bukti saksi, persangkaan, pengakuan dan sumpah. Kelima macam alat bukti tersebut, pada asasnya majelis hakim dalam sidang perkara perdata harus memberi kesempatan yang luas kepada para pihak yang berperkara tersebut untuk mengajukan suatu alat bukti guna menguatkan dalil-dalil gugatannya serta bantahannya, oleh karena itu peran alat bukti dalam persidangan sangat berperan penting untuk membuktikan suatu peristiwa yang disengketakan. Penelitian ini bertujuan untuk mengetahui, memahami, dan menganalisis kekuatan pembuktian affidavit sebagai alat bukti surat. Metode penelitian ini yaitu penelitian hukum normatif. Berdasarkan hasil pembahasan yang dilakukan oleh penulis bahwa affidavit merupakan pernyataan tertulis yang dibuat di bawah sumpah dan merupakan kewenangan dari notary public yang menganut sistem hukum common law. Dikategorikan sebagai alat bukti surat atau tulisan karena bentuk fisiknya yang diajukan dalam persidangan yaitu tertulis serta masih sebagai alat bukti surat biasa. Affidavit tidak bisa berdiri sendiri untuk pembuktian di pengadilan, oleh karena itu harus dibantu dengan alat bukti lain seperti keterangan saksi, alat bukti persangkaan, alat bukti pengakuan, dan Â alat bukti sumpah. Kata kunci: pembuktian, alat bukti, affidavit Â